Embodied Experiences Represented in Fishermen’s Children’s Writing across Ages in Pekalongan, Indonesia: A Cognitive Linguistic Perspective - Deli Nirmala (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Language represents the speaker’s identity due to the experiences stored in the mind that become mental lexicon used as expressions for communication. Fisherman children observing their fathers’ activities in fishing daily perceive what their parents do for their family. This article is aimed to describe the children’s feeling, experiences, and thought about fishermen through their words or expressions in their writing. To uncover the problems, I used observation method for collecting data; referential and inferential methods for analyzing data. I used elicitation technique to collect the data. The data were the words or expressions written by thirty seven fisherman children of SDN 01 API-API (elementary) SMP Fatkhul Qowim (junior secondary school), and MA Fatkhul Qowim (senior high school) in Wonokerto, Pekalongan, Indonesia. The results indicate that they use emotive vocabulary items which may result in their mental lexicon stored in the mind and fisherman vocabulary item preservation. Besides, they indicate fisherman habits, fishing trip duration, and natural challenges. The most prominent expressions are those referring to the main duties of fishing, natural challenges and hardship on the sea during fishing. Even the children have no direct experiences, they can perceive fisherman jobs quite well due to everyday observation.